Revitalizing criminological theory: towards a new ultra-realism - Hall, Steve (New directions in critical criminology, 2015)
Introduction -- Mainstream classical and contemporary theories -- The critical tradition -- The radical realist response -- Untangling the politics of criminological theory -- Ultra-realist criminological theory -- Conclusion: approaching the reality of our times